Development of antibacterial composite resin containing chitosan/fluoride microparticles as pit and fissure sealant to prevent caries. Issue 1 (31st December 2022) - Lai, Chun-Cheng; Lin, Chun-Pin; Wang, Yin-Lin
ABSTRACT: Objective: Develop a fissure sealant containing chitosan/fluoride microparticles (C/F) with antibacterial, fluoride release and recharge ability. Materials and Methods: Chitosan/fluoride microparticles were synthesized and added to Bis-GMA as C/F. The experimental group comprised 0%, 2%, 4% C/F, with Clinpro TM fissure sealant as control. Antibacterial activity was detected by Alamar Blue assay and colony-forming units (CFU). Biocompatibility was determined by WST-1 and LDH test. Curing depth, flowability, tensile strength and flexural strength were measured according to the ISO standard; microhardness by Vickers hardness test. Fluoride release and recharge were recorded through ionic chromatography. Statistical analysis was performed with an independent t-test, one-way and two-way ANOVA. P values less than 0.05 were considered significant. Results: 2% and 4% C/F showed antibacterial ability with CFU ratios decreasing to 10% and 25% respectively ( P < 0.01). Nonetheless, 4% C/F was concerned because biocompatibility revealed cytotoxicity compared to medium ( P < 0.001). 2% C/F had superior mechanical properties to Clinpro TM fissure sealant in terms of curing depth ( P < 0.001), microhardness and tensile strength ( P < 0.01). It had good fluoride release and recharge ability ( P = 0.67). Conclusions: 2% C/F could be an antibacterial sealant with good mechanical strength, fluoride release and recharge ability.